2020
DOI: 10.1002/smtd.202000447
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Chemical Potential of Crystal Growth Units to Tune the Bulk Structure of Nanocrystals

Abstract: The intrinsic factors affecting the bulk structures of nanocrystallites are not well explored during crystallization. In this study, it is demonstrated that the chemical potential of growth units plays decisive role in governing the final structure of nanocrystals. It is found that the types of reaction vessels are able to vary the chemical potential of growth units, and make the Pt and Pd nanocrystals (NCs) unexpectedly evolve from the cyclic penta‐twinned to the single‐crystal nanostructures. In turn, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…According to eq , the activation energy for the growth of a strained shell can be reduced by elevating the chemical potential in the reaction solutions. Generally, continuous injection of shell precursors at a high rate can guarantee a high chemical potential, which offsets the strain effect and consequently promotes the isotropic shell growth (Figure c) . In contrast, the strain-directed anisotropic shell growth becomes dominant at low precursor concentrations induced by slow injection of shell precursors into a large volume of the reaction mixture (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to eq , the activation energy for the growth of a strained shell can be reduced by elevating the chemical potential in the reaction solutions. Generally, continuous injection of shell precursors at a high rate can guarantee a high chemical potential, which offsets the strain effect and consequently promotes the isotropic shell growth (Figure c) . In contrast, the strain-directed anisotropic shell growth becomes dominant at low precursor concentrations induced by slow injection of shell precursors into a large volume of the reaction mixture (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, continuous injection of shell precursors at a high rate can guarantee a high chemical potential, which offsets the strain effect and consequently promotes the isotropic shell growth (Figure 2c). 32 In contrast, the strain-directed anisotropic shell growth becomes dominant at low precursor concentrations induced by slow injection of shell precursors into a large volume of the reaction mixture (Figure S4). Based on the strain-directed growth theory, the isotropic growth of NaLuF 4 shells over NaYbF 4 core nanoparticles in Figure S3 can be attributed to the balanced lattice mismatches at the lateral and basal facets, which are calculated as 0.49 and 0.47%, respectively (Table S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Supersaturation plays an important role in tailoring the morphology of the resultant nanomaterials and their exposed facets. For the chemical synthesis method, it usually relies on careful controlling of the reaction conditions (via, e.g., changing the type of the reducing agent, its injection rate, and the reaction temperature , ) to tune the supersaturation (which, in nature, is a homogeneous supersaturation of a bulk solution). For the collision electrochemical method, it not only can readily achieve this goal, realized just by changing the concentration of the growth solution, but also can create a local supersaturation just around the colliding NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, we found that by varying the chemical potential of growth units during the nucleation process, the evolution from cyclic penta‐twinned to single‐crystalline Pt nanostructures can be controlled. [ 12 ] Herein, we propose that the amorphous structures with high µ s can also be precisely controlled by governing high µ l in the nucleation process based on the similar consideration. PdCu alloy was first adopted as a typical example to verify the correctness of the above strategy.…”
Section: Introductionmentioning
confidence: 99%